PERUBAHAN SIFAT FISIKOKIMIA PISANG AMBON CURUP (Musa sapientum cv. ‘Ambon Curup’) SELAMA PENYIMPANAN MENGGUNAKAN Ca(OH)2 - SILIKA GEL SEBAGAI BAHAN PENUNDA KEMATANGAN [Physicochemical Changes of Ambon Curup Banana (Musa sapientum c.v. Ambon Curup) During Storage Using Ca(OH)2-Silica Gel as Material for Delaying Rippening] - Zulman Efendi; Lukman Hidayat (Jurnal Teknologi & Industri Hasil Pertanian, 2018)
Ambon Curup Banana is a local banana fruit grown in Rejang Lebong Regency, Bengkulu Province which has a short shelf life due to no material addition for delaying rippening. This study was conducted to evaluate the physicochemical changes of ‘Ambon Curup’ banana during storage with absorber of Ca(OH)2 and silica gel treatments. The research was conducted in a completely randomized design of one factor namely the composition of absorber Ca(OH)2 -silica gel: 0-0, 0-4, 0-8, 1-0, 1-4, 1-8, 3-0, 3-4 and 3-8  (% w/w) based on banana weight. The results showed that Ca(OH)2 3% with silica gel 4% and 8% were able to retain harder texture, inhibit the weight loss, green degradation, total soluble solid increase, and achieve better shelf life of 24 days at room temperature compared to other treatments.